2017
DOI: 10.1159/000471786
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Cannabidiol Induced Hypotension after Global Hypoxia-Ischemia in Piglets

Abstract: Background: Cannabidiol (CBD) is considered a promising neuroprotectant after perinatal hypoxia-ischemia (HI). We have previously studied the effects of CBD 1 mg/kg in the early phase after global HI in piglets. In contrast to prior studies, we found no evidence of neuroprotection and hypothesized that higher doses might be required to demonstrate efficacy in this animal model. Objective: To assess the safety and potential neuroprotective effects of high-dose CBD. Methods: Anesthetized newborn piglets underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Human studies administering CBD showed that the AUC 0−t and C max are dose-dependent, and T max mostly occurred between 1 and 4 h. Animal studies in piglets, mice, and rats also all demonstrate a dose-dependent relationship between CBD and both plasma and brain concentrations (Long et al, 2012 ; Hammell et al, 2016 ; Garberg et al, 2017 ), suggesting that human brain concentrations will also be dose-dependent. Ten publications in this review reported the half-life of CBD which ranged from 1 h to 5 days and varies depending on the dose and route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies administering CBD showed that the AUC 0−t and C max are dose-dependent, and T max mostly occurred between 1 and 4 h. Animal studies in piglets, mice, and rats also all demonstrate a dose-dependent relationship between CBD and both plasma and brain concentrations (Long et al, 2012 ; Hammell et al, 2016 ; Garberg et al, 2017 ), suggesting that human brain concentrations will also be dose-dependent. Ten publications in this review reported the half-life of CBD which ranged from 1 h to 5 days and varies depending on the dose and route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review conducted by our group, Millar, Stone, Yates, and O'Sullivan (2018) highlighted discrepancies regarding CBD bioavailability, C max , T max , and half‐life ( t 1/2 ) in humans depending on the route of administration and formulation and whether CBD was dosed in a fed or fasted state. That being said, studies conducted in piglets (Garberg et al, 2017) and rodents (Hammell et al, 2016; Long et al, 2012) have shown a dose‐dependent relationship between CBD administration and brain and plasma concentrations. Limited data extracted by Millar et al (2018) showed that administration of CBD in humans also led to dose‐dependent increases in plasma concentrations, suggesting the same may apply to brain concentrations in man.…”
Section: Discussionmentioning
confidence: 99%
“…This was to investigate more subtle interactions as the study does not have enough power to finally conclude, and hence the risk for a type II statistical error where we find false negatives and erroneously reject a false null hypothesis, has been present. In paper I we used a one-way ANOVA as had been used in the bilateral project of Garberg et al 99,209 , whereas in paper II and III we used a twoway ANOVA as this was suggested by reviewers in paper II. According to the statistical advice, both analyses can be used, but the strength of the two-way ANOVA is the interaction and the possibility to decipher which of the interventions in a factorial design (therapeutic hypothermia and DHA) have effects.…”
Section: Statistical Considerationsmentioning
confidence: 99%